2000
DOI: 10.1128/iai.68.5.2431-2434.2000
|View full text |Cite
|
Sign up to set email alerts
|

Are B Lymphocytes of Importance in SevereStaphylococcus aureusInfections?

Abstract: To investigate the role of B cells in experimental, superantigen-mediated Staphylococcus aureus arthritis and sepsis, we used gene-targeted B-cell-deficient mice. The mice were inoculated intravenously with a toxic shock syndrome toxin 1 (TSST-1)-producing S. aureus strain. The B-cell-deficient and thus agamma-globulinemic mice showed striking similarities to the wild-type control animals with respect to the development of arthritis, the mortality rate, and the rate of bacterial clearance. Surprisingly, we fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…5B). It was previously reported that B cells do not play a major role against S. aureus infections3861. On the contrary, our results seem to directly correlate decrease of B cell number in the joints and blood with the S. aureus early infection phase, suggesting that the pathogen might be directly involved in suppressing B cell responses systemically and in the joints, through different known mechanisms396263, and that this suppression might cause underestimation of the effective role of these cells in joint infections, as recently postulated in other models64.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…5B). It was previously reported that B cells do not play a major role against S. aureus infections3861. On the contrary, our results seem to directly correlate decrease of B cell number in the joints and blood with the S. aureus early infection phase, suggesting that the pathogen might be directly involved in suppressing B cell responses systemically and in the joints, through different known mechanisms396263, and that this suppression might cause underestimation of the effective role of these cells in joint infections, as recently postulated in other models64.…”
Section: Discussionmentioning
confidence: 98%
“…Mice have been considered good models for SA and OM3637, and since blood is the most frequent source of infection in humans737, efforts were made to set up and characterize an acute hematogenously-derived murine model of arthritis2528383940, with most of the reports being concentrated on observations made in the paws3637. Recently, also thanks to the great improvement in the preclinical imaging, other groups focused their attention in the field and were able to set up long lasting models of OM which evolved from an acute to a chronic phase264142.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the MyD88 knock-out mice, with defects in TLR/IL-1R/IL-18R signal transmission, are similarly to IL-1R knock-out mice, highly susceptible to S. aureus infection, MyD88-deficient mice being non-responsive to S. aureus with regard to proinflammatory cytokine response [6], while an intact innate immune response seems predominantly beneficial with regard to disease outcome, the role of the adaptive immune response in protection is less convincing. Firstly, absence of mature B cells does not aggravate septic arthritis [7], possibly due to the inability to produce protective antibodies to bacterial virulence factors [8] and/or a major polyclonal B cell activation [9]. Secondly, depletion of CD4+ cells ameliorates septic arthritis and decreases the risk of septic death, indicat-> The animal experiments were approved by the ethical committee of Göteborg, Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…Mice that were totally deleted for B cells using a gene-targeted approach and thus being agammaglobulinemic showed striking similarities to congeneic littermates with respect to the development of S. aureus arthritis and mortality [42]. This ¢nding indicates that the entire B cell compartment is of minor importance in the defence against severe S. aureus infection.…”
Section: Is Acquired Immune Responsiveness Bene¢cial or Detrimental Dmentioning
confidence: 76%